2014
DOI: 10.1177/003335491412900406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rapid Influenza Diagnostic Testing on Antiviral Treatment Decisions for Patients with Influenza-like Illness: Southwestern U.S., May–December 2009

Abstract: Rapid influenza diagnostic tests (RIDTs) had low test sensitivity for detecting 2009 pandemic influenza A (H1N1pdm09) infection, causing public health authorities to recommend that treatment decisions be based primarily upon risk for influenza complications. We used multivariate Poisson regression analysis to estimate the contribution of RIDT results and risk for H1N1pdm09 complications to receipt of early antiviral (AV) treatment among 290 people with influenza-like illness (ILI) who received an RIDT ≤48 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Likewise, Li‐Kim‐Moy et al (46.2% vs 21.5%, P = 0.001); Blaschke et al (56% vs 19%, P = 0.002); and Jennings et al (60.1% vs 24.6%, 4618/7658 vs 178/725) all reported that influenza positive patients had significantly increased antiviral use amongst those diagnosed by a POCT compared with standard testing. Blaschke et al also demonstrated antiviral prescription was significantly higher in patients who received a positive POCT result in comparison with a negative POCT result (56% vs 2%, P < 0.0001), as did Suryaprasad et al (57% vs 18%, 48/84 vs 37/206) and Theocharis et al (76.2% vs 1.1%, P < 0.01). One study of treatment outcomes showed that patients who were prescribed oseltamivir only were significantly more likely to have been diagnosed by POCT compared with patients receiving antibiotics only, antibiotic/antiviral combination, or supportive care.…”
Section: Resultsmentioning
confidence: 74%
“…Likewise, Li‐Kim‐Moy et al (46.2% vs 21.5%, P = 0.001); Blaschke et al (56% vs 19%, P = 0.002); and Jennings et al (60.1% vs 24.6%, 4618/7658 vs 178/725) all reported that influenza positive patients had significantly increased antiviral use amongst those diagnosed by a POCT compared with standard testing. Blaschke et al also demonstrated antiviral prescription was significantly higher in patients who received a positive POCT result in comparison with a negative POCT result (56% vs 2%, P < 0.0001), as did Suryaprasad et al (57% vs 18%, 48/84 vs 37/206) and Theocharis et al (76.2% vs 1.1%, P < 0.01). One study of treatment outcomes showed that patients who were prescribed oseltamivir only were significantly more likely to have been diagnosed by POCT compared with patients receiving antibiotics only, antibiotic/antiviral combination, or supportive care.…”
Section: Resultsmentioning
confidence: 74%
“…In a retrospective study of data from the National Hospital Ambulatory Medical Care Survey, influenza testing resulted in fewer ancillary and other diagnostic tests (ie, chest radiography, blood culture, urinalysis, complete blood count) and more frequent use of antivirals [136]. Another study reported that rapid influenza diagnostic testing resulted in early receipt of antiviral treatment as compared with relying on the presence of risk factors alone [137]. In a retrospective study, rapid influenza testing led to a significant reduction in antibiotic use among hospitalized adults [12].…”
Section: Diagnosismentioning
confidence: 99%
“…Few studies have evaluated the impact of influenza diagnostic testing on oseltamivir prescriptions [ 6 , 8–11 ]. It is noteworthy that 3 studies were based on antigen-based diagnosis tests, which are known for their poor sensitivity [ 8 , 10 , 11 ]. Trabattoni et al [ 6 ] compared the impact of another rapid molecular diagnosis test (Alere i Influenza A and B Assay) when it was performed in the clinical ward or in the laboratory, and they did not find any difference in oseltamivir prescriptions.…”
Section: Discussionmentioning
confidence: 99%